THE EFFECT OF MARRIAGE COMMITMENT AND MARRIAGE ADJUSTMENT TOWARD MARRIAGE SATISFACTION OF GBKP PRIEST’S WIFE - Karina Meriem Beru Brahmana; Hotpascaman Simbolon; Artiwinata Br Ginting; Tata Lithani Hawi Shinta Udek; Winny Sevthyade Manalu (Universitas Ahmad Dahlan, 2023)
This study aims to see whether there is an effect of marriage adjustment and marriage commitment on marriage satisfaction of the GBKP pastor's wife. Being the wife of a GBKP pastor is not easy. The pastor's many duties, where the congregation requires more attention, tends to make the wife feel neglected. Due to the large number of services that husbands have to perform in their daily lives, this causes husbands to tend not to be able to help with child care or help with domestic tasks because time is not possible. This research was conducted on the wives of GBKP pastors who have been married for at least 1 year and have been blessed with at least 1 child. This study uses 3 measurement tools, namely the Kansas Marriage Satisfaction scale compiled by Schumm (1986) to measure marriage satisfaction. Marriage adjustment was measured using The Dyadic Adjustment Scale (DAS) from Spanier (1976). while marriage commitment is assessed by the Marriage Commitment Scale developed by Stanley and Markman (1992), which consists of eight items. The results of the study using the regression test show that marriage commitment and marriage adjustment simultaneously affect marriage satisfaction significantly.